Prescription Drug Recalls on Florida's Medicaid Preferred Drug List - Josephine M. Kershaw; A. Mark Freeman; Charisma Y. Atkins; Marisa A. Lewis (University of North Florida, 2005)
Prescription drug use is rising among Americans in all age groups. In general, utilization of prescription medications increases with age due to chronic health conditions that require pharmaceutical interventions. Because Medicaid is the single largest payer of prescription medications in Florida, this study's objectives were to: (1) examine Medicaid spending on recalled drugs for the 2001-02 fiscal year, (2) assess Medicaid expenditures for comparison drugs on the Medicaid preferred drug list for the same time period, and (3) contrast the drugs that received fast track approval with those undergoing standard approval. In this study, Medicaid spending for recalled drugs was much lower than comparison drugs on the preferred drug list, in part because of a fewer number of claims and associated dispensing fees. On the other hand, a higher percentage of recalled drugs had received fast track review than comparison drugs which were more likely to utilize the standard approval process. Given the widespread use of prescription drugs, it is essential to assure the efficacy and safety of new medications prior to consumption by the general public, particularly because of their higher cost and impact on health expenditures.